Distributional Learning of Speech Sounds: An Exploratory Study Into the Effects of Prior Language Experience. Issue 1 (9th September 2020) - Chládková, Kateřina; Šimáčková, Šárka
Abstract: Distributional learning is typically understood as (unattended) tracking of stimulus probabilities. Distributional training with speech yields mixed results and the influencing factors have not yet been fully investigated. This study explored whether prior linguistic experience could have an effect on distributional learning outcomes. Czech and Greek adults, whose native languages contain and lack abstract length categories, respectively, were exposed to novel vowels falling into unimodal or bimodal distributions along the durational dimension. A trending interaction suggested that the Czechs and the Greeks might have been affected differently by the distributional exposure. Improved discrimination of the "trained" contrast was observed in bimodally exposed Czechs (whose prior expectations about length categories could guide learning) and, rather surprisingly, in unimodally exposed Greeks (who, lacking any expectations, might have listened in a noncategorical, auditory mode). Prior linguistic experience could thus affect whether and how experienced language users exploit new distributional speech statistics. This proposal needs to be assessed in future studies. Abstract :